Sonographic Quantification of Ovarian Volume in Adults Attending General Health Checkup and General Out Patient Department in Tribhuvan University Teaching Hospital - Upadhyaya, R. P.; Ansari, M. A.; Jha, A.; Kayashta, P.; Paudel, S. (Kathmandu University Medical Journal, 2020)
Background Ultrasonography is the easily available, cheap and reliable method for evaluation of ovaries. Ovarian volume is the major factor in the diagnosis of various ovarian pathologies and confusing discrepancies are found in the literature. Objective To determine the ovarian volume among individuals attending outpatient department in tertiary level hospital. Method Descriptive cross sectional study design was used; 305 patients of 16-60 years attending general outpatient department in the Tribhuvan University Teaching Hospital, Kathmandu, Nepal were included. Ovarian volume was calculated by using transabdominal ultrasonography. Data was collected in the predesigned proforma and analyzed using statistical package for the social sciences software. Result The study showed mean total ovarian volume 5.95 ± 2.44 cc (centimeter cube) with mean right ovarian volume 5.94 ± 2.70 cc and mean left ovarian volume 6.05 ± 2.79 cc. Significant decrease in ovarian volume with age was observed. Height and weight did not show significant correlation with ovarian volumes and no significant variation seen in the volumes of right and left ovaries. Periovulatory ovaries show significantly higher volumes on right side than luteal phase. Similarly, significantly higher volume of left ovary seen in mixed ethnic group than mongoloid group. Conclusion Measurement of ovarian volume is important for evaluation and management of ovarian disorders. Ultrasonography which is readily available, simple and cost effective is better suited for our environment than other imaging modality. Values of ovarian volume from this study may provide a baseline of normal ovarian volume in our community.